Piracy, maritime terrorism and securing the Malacca Straits - Ong, Graham Gerard 1975- (IIAS/ISEAS series on maritime issues and piracy in Asia., 2006)
Part of a series on Maritime Issues and Piracy in Asia by the International Institute of Asian Studies, Leiden University, and the Institute of Southeast Asian Studies, this volume includes fresh perspectives to the debate about piracy, the threat of maritime terrorism, and the challenge of securing the Malacca Straits.